Defectoscopic examinations of railway rails - Łukasz Rawicki; Jacek Słania (Przegląd Komunikacyjny)
Abstract: Non-destructive testing is a key element in ensuring the safe operation of the railway track. They allow for the detection of discontinuities arising both at the stage of production and operation. However, non-destructive testing has some limitations due to its nature. The vast majority of them are indirect methods in which the occurrence of discontinuities is inferred from the course of specific physical phenomena. Non-destructive testing methods provide information about the properties of the tested object. Their goals are to detect and estimation the nature of the discontinuities. The article presents some of the methods that can be used in the examination of railway rails, such as visual and ultrasonic tests. Attention was also paid to unconventional tests used in practice and allowing the detection of discontinuities, such as the method of the scatter field flux and the measurement of the alternating current field. Keywords: VT research; MFL method; MPM method; AFCM method; UT method, PA technique